PERCEPTIONS ON THE EFFECTIVNESS OF USING SONGS IN TEACHING ENGLISH AT SMAN MODEL TERPADU MADANI PALU - Vicha Hulai, Bella; Aminah, Aminah; Dewi, Anjar Kusuma; Marhum, Mochtar (e-Journal of ELTS (English Language Teaching Society), 2024)
The Songs can provide attractive and instructional media in learning activities. Song has been designed to motivate students to participate the English teaching and learning. The study aims to identify the students’ perception on using songs in teaching English. Interviews are conducted as the research instruments to get students’ perceptions towards English songs in teaching English. The interviews show that most students feel English songs are very helpful for them in improving their Speaking skill. They also feel that the English song they listen to have the power to encourage students' motivation to learn the. Correct pronunciation and learn English more deeply. In addition, the beauty of the tone and rhythm of the music also makes students feel happy and relaxed. They also feel that by listening to the lyrics of English song carefully, they can easily get information about the correct pronunciation from native speakers. It makes them enthusiastic and increases their interest in learning.